Analisis dan Perencanaan Konsep Strategi Content Management Cyberwoman pada Situs Portal CBN.Net.Id - Liawatimena, Suryadiputra (Journal the Winners: Economics, Business, Management, and Information System Journal, 2007)
Article discusses how the CyberWoman management strategy on CBN portal site to serve many information, service, and recovery concept that will be used for its better growing. The article purposes are to know whether the content management strategy of portal site applied by CBN, especially for CyberWoman, has been running well or not and also give a recovery concept in the future. The conclusion indicates that the CBN have opportunity and strength that can be used and the CBN portal site is in the state of growing. Therefore, the applied strategy is an aggressive growing policy strategy and concentration strategy through horizontal integration.